2021
DOI: 10.1186/s40816-021-00248-6
|View full text |Cite
|
Sign up to set email alerts
|

Overview on pharmacovigilance of nephrotoxic herbal medicines used worldwide

Abstract: Materials and methods Search strategyElectronic literature searches were conducted in Mai 2020 to identify case reports of nephrotoxicity associated with herbal medicines use in the last two decade. The scientific resources including PubMed, Scopus, and Science direct were searched using key words such as: 'case report', 'Renal side effect', 'adverse effects', 'Nephrotoxicity', 'Risk', 'Herbal Medicine', 'kidney disease'. The spectrum of herbal induced kidney injuries included kidney stones, nephritis, nephrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The theoretical basis of the method is constructed as follows: the physicochemical properties of a certain ragwort can be derived by analogy from a similarly structured ragwort. Also, this method saves unnecessary testing time by avoiding the need to test a large number of similar ragworts [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical basis of the method is constructed as follows: the physicochemical properties of a certain ragwort can be derived by analogy from a similarly structured ragwort. Also, this method saves unnecessary testing time by avoiding the need to test a large number of similar ragworts [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The machine learning algorithm has certain advantages in dealing with problems such as large sample size and multi-dimension. Traditional machine learning algorithms include decision trees, random forests (RFs), support vector machines (SVMs), plain Bayesian, k-nearest neighbour methods, and so on [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Suk et al suggested that DILI is a highly relevant health problem in Korea, and HMs are the most common cause of DILI. [10] Furthermore, Touiti et al reported that HMs presented an actual risk to the kidney, [11] and Yang et al reviewed several causes of kidney damage from HMs. [12] Generally, patients with stroke are older and take several CMs, increasing the possibility of hepatotoxicity and nephrotoxicity from multidrug interactions when combined with long-term HM use; these events may lead to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Suk et al suggested that DILI is a highly relevant health problem in Korea, and HMs are the most common cause of DILI. [10] Furthermore, Touiti et al reported that HMs presented an actual risk to the kidney, [11] and Yang et al reviewed several causes of kidney damage from HMs. [12]…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacovigilance about over-the-counter (OTC) medications that pharmacists dispense in pharmacies is crucial (Sinclair et al 1999;Layton et al 2002;Touiti et al 2021). Lower than 50% of pharmacists thought it was crucial to ADRs reporting brought on by over-the-counter medications.…”
Section: Discussionmentioning
confidence: 99%